Persepsi Ibu tentang Pentingnya Deteksi Dini Tumbuh Kembang Anak di Posyandu Desa Parsanga - Rasyidah Rasyidah; Abd Wahid; Maulana Widi Andrian (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2022)
The goal of this study was to find out how mothers in Posyandu Betet, Parsanga Village, felt about the importance of DDTK for their children. This study employs a quantitative, using a total sampling technique with 18 mothers who came with their children at the Posyandu in Parsanga Village. The result is, most of mothers had a negative perception. The negative category of mother's perception was shown in the aspect of judgment and aspect of understanding. According to the findings, parents, particularly mothers, should pay attention about children growth and development in order their childrens in an optimsl growth based on their age.